Health checkup, fitness, and complementary therapy in Muntilan library and archives service, Magelang, Central Java - Nurul Hidayah; Sambodo Sriadi Pinilih; Robiul Fitri Masithoh; Enik Suhariyanti; Daryati Retno Cahyaningsih; Nurul Niawati; Prasetyo Budi Utomo (Universitas Ahmad Dahlan, 2023)
Muntilan is a sub-district in Magelang Regency, Central Java, Indonesia, located 10 km from Mungkid district, 15 km from Magelang city, and 25 km from Yogyakarta city. Muntilan is on the provincial route connecting Semarang city, Magelang city, and Yogyakarta city. This community service activity is carried out as a form of concern for improving the health status of the community. This activity was held on 27th - 28th November 2019 in Muntilan Library and Archives Service, Magelang, Central Java. The targets of this activity are the residents of Muntilan and the staff of the Muntilan Library and Archives Service, Magelang, Central Java. This activity uses the method of providing information through health checks, fitness, and complementary therapies. This activity was attended by 151 people (71 people on 27th November 2019 and 80 people on 28th November 2019). The service team carried out health checks in the form of a health history, blood pressure checks, Temporary Blood Sugar, uric acid, height and weight checks, complementary therapy, health counseling, and fitness consultations.